2018
DOI: 10.1101/294835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Functional selectivity and specific connectivity of inhibitory neurons in primary visual cortex

Abstract: In the cerebral cortex, the selectivity of neurons for features of sensory stimuli arises through the interaction of excitatory and inhibitory synaptic inputs. Excitatory neurons receive inhibitory input that closely tracks excitation 1-4 , stabilizing network dynamics 5 while improving efficiency and robustness of the neural code 6-8 . However, how this balance of excitation and inhibition is achieved by cortical circuits is unclear, since inhibitory interneurons are thought to pool the inputs of nearby excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
136
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(164 citation statements)
references
References 30 publications
(64 reference statements)
28
136
0
Order By: Relevance
“…We found that to obtain feature-specific suppression, strong and functionally-specific subnetworks of E and I were necessary. That is, both E and I neurons with similar receptive fields (RFs) should be connected together more strongly than their non-similar counterparts, which was consistent with recent results in visual cortex (Znamenskiy et al, 2018).Our modelling results shed light on the above mentioned controversy by showing that featurespecific amplification and suppression could both exist in the cortex, depending on the regime of functional similarity between the influencers and the influencees. Our model suggests specific predictions on how to observe this in the cortex.…”
supporting
confidence: 90%
“…We found that to obtain feature-specific suppression, strong and functionally-specific subnetworks of E and I were necessary. That is, both E and I neurons with similar receptive fields (RFs) should be connected together more strongly than their non-similar counterparts, which was consistent with recent results in visual cortex (Znamenskiy et al, 2018).Our modelling results shed light on the above mentioned controversy by showing that featurespecific amplification and suppression could both exist in the cortex, depending on the regime of functional similarity between the influencers and the influencees. Our model suggests specific predictions on how to observe this in the cortex.…”
supporting
confidence: 90%
“…Recent studies in rodents have began to genetically target distinct cell-types to study their precise contributions to sensory tuning and network oscillations. These studies support a role for inhibition in shaping orientation-and direction-selectivity of V1 neurons (Kerlin et al, 2010;Znamenskiy et al, 2018;Perrenoud et al, 2016). Furthermore, they have implied specific classes of inhibitory interneurons in the generation of V1 gamma oscillations in mice (Veit et al, 2017;Chen et al, 2017;Senzai et al, 2019;Perrenoud et al, 2016).…”
Section: E-i Interactions Aresupporting
confidence: 64%
“…Another recent study (Znamenskiy et al, 2018) suggested that targeted connectivity between 422 excitatory and inhibitory neurons allows for the existence of highly selective excitatory 423 subnetworks, while keeping the network stable. In circuits with non-selective inhibition, by 424 contrast, excitatory subnetworks had to be weakly selective in order to keep the network stable 425 (Znamenskiy et al, 2018). The permissiveness to highly selective excitatory subnetworks in 426 circuits with selective inhibition may be advantageous for situations that require precise 427 encoding of sensory stimuli for discrimination.…”
Section: Discussion 398mentioning
confidence: 99%